Memahami Ajaran Tamansiswa Secara Mendasar Di Desa Cepor Kidul - Eko Susetyo; Pristin Prima Sari; Tasya Uli Adelia Hannum (LPPM ITB AAS Indonesia Surakarta, 2022)
The activity aims to present Tamansiswa’s Teaching in Cepor Kidul Village Kapanewon Bantul Yogyakarta. The Participants are community and university student of Sarjanawiyata Tamansiswa. The method using discussion and publication on Youtube online channel. The output such as an understanding about Tamansiswa principle and teaching as the following Asah-Asih-Asuh, Hidup Tertib Salam Dan Bahagia, and Tri-N (Niteni, Niroke, Nambahi) and glorious cultural on implementation and learning in Cepor Kidul Village. The Media of activity using Brosur about Tamansiswa Principle and Tamansiswa's teaching. The outcome is photo and publication on youtube. Keywords : Tamansiswa's Teaching, Society, community services.